Action of anticytoskeletal compounds on in vitro cytopathic effect, phagocytosis, and adhesiveness of Trichomonas vaginalis. Issue 4 (August 1987) - Juliano, C; Monaco, G; Bandiera, P; Tedde, G; Cappuccinelli, P
Abstract : The cytopathic effects of Trichomonas vaginalis treated with inhibitory concentrations of anticytoskeletal compounds (mebendazole, griseofulvin, colchicine, taxol, and cytochalasin B) were studied in mouse CLID fibroblast cultures. The evaluation, at different times, of cell numbers and morphological alterations showed that cytopathic effect was considerably reduced when protozoa were pretreated with mebendazole and griseofulvin, whereas colchicine, taxol, and cytochalasin B had less effect. Furthermore, treatment with mebendazole, griseofulvin, and colchicine decreased adhesiveness of the protozoan, whereas treatment with cytochalasin B and colchicine completely inhibited its phagocytic activity. From these results it may be concluded that alterations induced in the trichomonal cytoskeleton may affect its adhesiveness and its in vitro cytopathic effect, but there is no direct correlation between protozoan phagocytosis and its in vitro pathogenic effect.